Le Cadre Spatio-Temporel Romanesque Au Service De L’ecriture Feminine (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Résumé : Le Temps Et L’espace Sont Le Cadre Dans Lequel S’inscrit Tout Récit Romanesque, Ils Peuvent Accentuer L’intensité Dramatique Autour Du Récit D’où Leur Importance. Assia Djebar A Tout Au Long De Son Œuvre Installé Les Femmes Dans Des Espaces Clos Où Le Temps Est Difficile A Faire Passer Paradoxalement Aux Hommes Qui Usent Des Espaces A Leurs Grès, C’est Cette Dichotomie Spatio-Temporel Qui Agit Sur La Psychologie Des Personnages Tout En Contribuant A Leurs Représentations Et Fait D’eux Un Signe Que Nous Nous Proposons D’explorer.Mots-Clés : Représentations, Cadre Spatio-Temporel, Ecriture Féminine, Maîtrise, Désorganisation. Abstract: Time And Space Are The Framework In Which Any Novelistic Narrative Is Inscribed, They Can Accentuate The Dramatic Intensity Around The Story Hence Their Importance. Assia Djebar Has Throughout Her Work Placed Women In Closed Spaces Where Time Is Difficult To Pass Paradoxically To The Men Who Use The Spaces To Their Liking. It Is This Spatio-Temporal Dichotomy That Acts On The Psychology Of The Characters While Contributing To Their Representations And Makes Them A Sign That We Propose To Explore.Keywords: Representations, Spatio-Temporal Framework, Female Writing, Mastery, Disorganization